The Role of Teaching Music in the Conditions of Computerization - Cicović Sarajlić, Dragana J.; Kovač, Anđelka M.; Milentijević, Ester F. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Using analytical methods, the paper discusses the role of teaching the subject of Musical Culture in the conditions of computerization and digitalization. Providing a wide variety of opportunities such as research, learning and education, as well as the pleasure of entertainment and leisure, information and communication technology has become an integral part of the life of modern man. Teaching and learning are processes that are inevitably conditioned by the overall technical and technological development and societal progress. In modern education, computerization is considered one of the essential conditions for its successful implementation. Students are expected to use all available resources, and above all information, in the process of acquiring knowledge. As numerous scientific and research works point to the need and importance of using modern information technology in education, there are also those who warn of negative effects when using it. Namely, in search of information, students find themselves on the Internet and encounter unverified information, as well as contents that are inappropriate for their age. Likewise, it was observed that young people spend most of their free time on computers, mobile phones and tablets, which affects their social life and engagement in physical activities. As a result of long-term and excessive use of these devices, health problems such as eye fatigue, poor concentration, headaches, and neck pain are occurring more frequently. In addition, the dependence on social networks, the social withdrawal and isolation of young people, and the increasingly pronounced alienation they experience should also be pointed out. Therefore, in the process of education and upbringing, it is necessary to use available pedagogical knowledge and experience to overcome these phenomena, which undoubtedly represent a social problem. In this sense, the goal of this work was to determine how the teaching of musical culture can contribute to the proper social education of students under the conditions of computerization. It is undeniable that the teaching of musical culture contributes to the overall development of each individual and to the social and collective growth. When properly used, musical contents and activities such as: singing, performing musical games, listening to music or playing children’s musical instruments, which are usually performed in a group, represent a significant pedagogical opportunity for the development of social skills in students. In the conditions of general digitalization and computerization, this is a value that should be paid special attention to.
Keywords: computerization; music teaching; sociability; students